Web Photoshop 5 to go - Miletsky, Jason I. (Prentice Hall PTR, 1999)
"Web Photoshop To Go" distills the most critical information Web experts know about Photoshop into a fast-paced, easy-access guide designed for "experienced Photoshop users." This is a solutions-oriented guide to every aspect of Web design with Photoshop.